2009
DOI: 10.1176/appi.ap.33.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Bullying of Trainee Psychiatrists in Pakistan: A Cross-Sectional Questionnaire Survey

Abstract: Most postgraduate psychiatry trainees in Pakistan have experienced bullying. Measures need to be taken to increase awareness of what constitutes bullying and how it affects its victims. It may be necessary to introduce antibullying policies at least at the organizational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Data were gathered by means of an anonymous questionnaire distributed among the participants during identify specific stressful life experiences, though several respondents commented on the relationships with both other professionals as well as patients as a major source of stress. In the case of chronic stress, leading to underperformance [40], high satisfaction with career support, high sense of coherence [34,41], occupational self-efficacy [34], and low values regarding being overcommitted to ones work [35] seem to act as protective factors.…”
Section: Participantsmentioning
confidence: 99%
“…Data were gathered by means of an anonymous questionnaire distributed among the participants during identify specific stressful life experiences, though several respondents commented on the relationships with both other professionals as well as patients as a major source of stress. In the case of chronic stress, leading to underperformance [40], high satisfaction with career support, high sense of coherence [34,41], occupational self-efficacy [34], and low values regarding being overcommitted to ones work [35] seem to act as protective factors.…”
Section: Participantsmentioning
confidence: 99%
“…12 13 Maltreatment of medical trainees is not limited to Western countries. 14- 16 Ahmer et al 17 have reported pervasive and persistent tendencies for medical trainees in Pakistan to be subjected to 'disrespectful interactions', 'belittlement', 'undermining' and 'humiliation'. Drawing on the available literature, Coverdale et al 5 categorised the common forms of maltreatment directed towards medical trainees as verbal abuse or humiliation, non-sexual harassment, sexual harassment and forms of prejudice against sexual orientation or ethnicity.…”
Section: P269)mentioning
confidence: 99%
“…3,6 The prevalence of workplace bullying throughout the medical workforce in Australia or elsewhere has not been investigated, with previous studies focussing on subsets of doctors, particularly junior doctors. 2,3,[9][10][11][12][13][14][15][16][17] We report here on cross-sectional data gathered through the DeC Study on the prevalence and potential impact of bullying in the Australian medical workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first to examine bullying within a cross-section of a national medical workforce and with 747 respondents, is amongst the largest published studies investigating this issue. Previous studies have investigated the prevalence of bullying in specific sectors of the workforce, including junior doctors, 2,11,12,14,17 trainee psychiatrists, 10 postgraduate hospital dentists, 15 and staff of specific regional health administrations. 13,28 However, comparisons between studies are difficult because different definitions of bullying and data collection methods were used.…”
mentioning
confidence: 99%